Efficacy of denosumab co-administered with vitamin D and Ca by baseline vitamin D status - Sugimoto, Toshitsugu; Matsumoto, Toshio; Hosoi, Takayuki; Shiraki, Masataka; Kobayashi, Makiko; Okubo, Naoki; Takami, Hideo; Nakamura, Toshitaka (Journal of bone and mineral metabolism, 2020)
Introduction In anti-osteoporosis drug trials, vitamin D and calcium (Ca) are common supplements; however, the optimal dose of each is unclear. Using data from the randomized, double-blind, placebo-controlled DIRECT trial, we assessed whether baseline serum 25-hydroxy vitamin D (25[OH]D) level influences the efficacy of denosumab co-administered with vitamin D and Ca. Materials and methods In this prespecified sub-analysis, subjects with primary osteoporosis who received denosumab or placebo, plus vitamin D (≥ 400 IU/day) and Ca (≥ 600 mg/day), were classified as 25(OH)D deficient (< 20 ng/mL), insufficient (≥ 20 to < 30 ng/mL), and sufficient (≥ 30 ng/mL). Study endpoints included absolute serum 25(OH)D level at baseline, 12 months, and 24 months; change in serum 25(OH)D and bone mineral density (BMD) status from baseline; and incidence of new vertebral fractures at 24 months. Results In 475 denosumab-treated and 481 placebo-treated subjects, proportions with deficient/insufficient/sufficient 25(OH)D at baseline were 53.1%/37.1%/9.9% and 50.9%/42.0%/7.1%, respectively. Supplementation significantly increased mean serum 25(OH)D levels; at 24 months, mean levels were > 30 ng/mL (sufficient) in both treatment groups. Increase in BMD over time was higher in the denosumab group vs. placebo group in all three vitamin D status groups. At month 24, denosumab-treated subjects with deficient/insufficient baseline 25(OH)D had a significantly lower risk of new vertebral fracture vs. placebo-treated subjects. Conclusion Among DIRECT trial subjects supplemented with ≥ 400 IU/day of vitamin D and ≥ 600 mg/day of Ca, baseline 25(OH)D sufficiency may not influence the efficacy of denosumab in increasing BMD or preventing vertebral fractures.